Network Analysis from the Edge Binding Number for Coprime graph of Groups - A. Mallika, A. Mallika; Ansari, J. Ahamed Thamimul (Journal of Neonatal Surgery, 2025)
Binding number is used to quantify the network's vulnerability as a parameter from the viewpoint of neighborhood structure. A graph represents the network, and min is the Edge binding number of . Let be a vertex set, where is a finite group with identity . If two distinct vertices and b are connected if and only if . This is called the coprime graph of and its denoted by . In this paper, we investigate the exact for the network settings that are constructed as and discussed its bound range.